Low‐to‐Mid Al Content (x = 0–0.56) AlxIn1−xN Layers Deposited on Si(100) by Radio‐Frequency Sputtering. Issue 4 (24th January 2020) - Blasco, Rodrigo; Valdueza-Felip, Sirona; Montero, Daniel; Sun, Michael; Olea, Javier; Naranjo, Fernando B.
Abstract : Radio‐frequency (RF) sputtering is a low‐cost technique for the deposition of large‐area single‐phase AlInN on silicon layers with application in photovoltaic devices. Here, the effect of the Al mole fraction x from 0 to 0.56 on the structural, morphological, electrical, and optical properties of n‐Al x In1− x N layers deposited at 550 ºC on p‐Si(100) by RF sputtering is studied. X‐ray diffraction data show a wurtzite structure oriented along the c ‐axis in all samples, where the full width at half maximum of the rocking curve around the InN (0002) diffraction peak decreases from ≈9° to ≈3° while incorporating Al to the AlInN layer. The root‐mean‐square surface roughness, estimated from atomic force microscopy, evolves from 20 nm for InN to 1.5 nm for Al0.56 In0.44 N. Low‐temperature photoluminescence spectra show a blueshift of the emission energy from 1.59 eV (779 nm) for InN to 1.82 eV (681 nm) for Al0.35 In0.65 N according to the Al content rise. Hall effect measurements of Al x In1− x N (0 <  x  < 0.35) on sapphire samples grown simultaneously point to a residual n‐type carrier concentration in the 10 21  cm −3 range. The developed n‐AlInN/p‐Si junctions present promising material properties to explore their performance operating as solar cell devices. Abstract : High‐quality and single‐phase n‐type Al x In1− x N layers ( x  = 0–0.56) on p‐Si(100) are successfully deposited by radio‐frequency magnetron sputtering. Increasing the Al content to 56% improves the structural and morphological layers quality. However, the AlInN resistivity increases, whereas the carrier concentration and mobility decrease. Samples show strong room‐temperature photoluminescence, which blueshifts from 1.57 eV (InN) to 1.77 eV (Al0.35 In0.65 N).